The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.18632/oncotarget.5322
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide inducible clone-5 mediates reactive oxygen species signaling for hepatocellular carcinoma progression

Abstract: One of the signaling components involved in hepatocellular carcinoma (HCC) progression is the focal adhesion adaptor paxillin. Hydrogen peroxide inducible clone-5 (Hic-5), one of the paralogs of paxillin, exhibits many biological functions distinct from paxillin, but may cooperate with paxillin to trigger tumor progression. Screening of Hic-5 in 145 surgical HCCs demonstrated overexpression of Hic-5 correlated well with intra- and extra-hepatic metastasis. Hic-5 highly expressed in the patient derived HCCs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 47 publications
3
43
0
3
Order By: Relevance
“…1D , upper panel). Moreover, TPA can induce activation of MMP9-950 and ZEB1-1079 by 35.0- and 7.0-fold, respectively, in HCC340, a patient derived HCC cell line 24 (Fig. 1D , lower panel).…”
Section: Resultsmentioning
confidence: 99%
“…1D , upper panel). Moreover, TPA can induce activation of MMP9-950 and ZEB1-1079 by 35.0- and 7.0-fold, respectively, in HCC340, a patient derived HCC cell line 24 (Fig. 1D , lower panel).…”
Section: Resultsmentioning
confidence: 99%
“…Another molecule, hydrogen peroxide-inducible clone-5 (Hic-5) is a TGF-β1-inducible focal adhesion protein that facilitates cell proliferation and ECM expansion in various organs[67]. Previous studies have shown that Hic-5 contributes to vascular restoration and restructuring[67,68]; however, a recent study revealed that Hic-5 expression also plays a critical role in attenuating fibrosis by enhancing TGF-β-induced Smad2 phosphorylation via the downregulation of Smad7 in both human and mouse aHSCs[69]. Taken together, these data indicate that Hic-5 is a novel therapeutic target and a potential marker of activated HSCs.…”
Section: Novel Therapeutic Targets In Liver Fibrosismentioning
confidence: 99%
“…Different reports suggest for Hic-5 implications in malignant diseases, as Hic-5 has been intensively studied for its role in modulating the TGFβ signaling pathway and ECM remodeling during prostate cancerogenesis [ 10 , 11 , 17 , 30 , 36 - 40 , 54 - 57 ]. Similarly, Hic-5-mediated regulatory functions were shown to induce metastasis in breast cancer [ 14 , 32 , 55 ], melanoma [ 33 ] and hepatocellular carcinoma [ 58 ].…”
Section: Discussionmentioning
confidence: 99%